Neurons in the lateral intraparietal area create a priority map by the combination of disparate signals - Ipata, Anna E. (2008)
Primates search for objects in the visual field with eye movements. We recorded the activity of neurons in the lateral intraparietal area (LIP) in animals performing a visual search task in which they were free to move their eyes, and reported the results of the search with a hand movement. We distinguished three independent signals: (1) a visual signal describing the abrupt onset of a visual stimulus in the receptive field; (2) a saccadic signal predicting the monkey's saccadic reaction time independently of the nature of the stimulus; (3) a cognitive signal distinguishing between the search target and a distractor independently of the direction of the impending saccade. The cognitive signal became significant on average 27 ms after the saccadic signal but before the saccade was made. The three signals summed in a manner discernable at the level of the single neuron.